Модернізація промисловості регіонів в контексті територіальної та функціональної децентралізації - Ляшенко, В.І.; Солдак, М.О. (Вісник економічної науки України, 2018)
Статтю присвячено питанням модернізації промисловості регіонів в контексті територіальної та функціональної децентралізації. Виявлено та співставлено деякі сучасні тенденції децентралізації та реформування територіального устрою в Італії, Франції та Німеччині. Запропоновано виділення в Україні восьми економічних районів, як неадміністративних агрегацій, що утворюються шляхом об’єднання менших адміністративних одиниць (областей) з урахуванням соціально-економічного, культурного, історичного аспектів, та формуються навколо наукових центрів НАН України та МОН України, і відповідають рівню NUTS 1 за номенклатурою територіальних одиниць ЄС. Визнання наукових центрів ключовими акторами формування регіональної інноваційної системи економічного району дає можливість говорити про появу нових форм досягнення функціональної децентралізації, завдяки формуванню мережі акторів (наукових центрів НАН України та МОН України), які зорієнтовані на виконання конкретних функцій з метою науково-інноваційного забезпечення модернізації промисловості. Статья посвящена вопросам модернизации промышленности регионов в контексте территориальной и функциональной децентрализации. Выявлены и сопоставлены некоторые современные тенденции децентрализации и реформирования территориального устройства в Италии, Франции и Германии. Предложено выделение в Украине восьми экономических районов, как неадминистративных агрегаций, образующиеся путем объединения меньших административных единиц (областей) с учетом социально-экономического, культурного, исторического аспектов, которые формируются вокруг научных центров НАН Украины и МОН Украины и соответствуют уровню NUTS 1 номенклатуры территориальных единиц ЕС. Признание научных центров ключевыми акторами формирования региональной инновационной системы экономического района дает возможность говорить о появлении новых форм достижения функциональной децентрализации, благодаря формированию сети акторов (научных центров НАН Украины и МОН Украины), которые ориентированы на выполнение конкретных функций с целью научно-инновационного обеспечения модернизации промышленности. The article deals with modernization of the regional industry in the context of territorial and functional decentralization. Some modern tendencies of decentralization and reformation of the territorial structure in Italy, France and Germany are identify and compared. It is proposed to allocate eight economic regions in Ukraine as non-administrative aggregations, formed by combining smaller administrative units (regions), taking into account the socio-economic, cultural, historical aspects that are formed around the scientific centers of the National Academy of Sciences of Ukraine and the Ministry of Education and Science of Ukraine and correspond to the level of NUTS 1 Nomenclature of Territorial Units for Statistics (Eurostat). Recognition of scientific centers as key actors in the formation of the regional innovation system of the economic region makes it possible to talk about the emergence of new forms of achieving functional decentralization, thanks to the formation of an actors network (scientific centers of the National Academy of Sciences of Ukraine and the Ministry of Education and Science of Ukraine), which are focused on performing specific functions with the aim of scientific and innovative provision of industrial modernization.